Tren Pengembangan Aplikasi Mobile: Sebuah Tinjauan Literatur - Shabrina Ziha Fidela; Meisye Putri Azizah; Septia Rizka Hidayah (Pusat Riset dan Inovasi Nasional, 2023)
The development of technology towards mobile application trends has become an important part of everyday life. This development trend provides some transformation in various industrial sectors that can increase productivity, so a deep understanding of this mobile application development trend is needed. This research aims to give systematically review trends which is used in mobile application development in Indonesia using the Systematic Literature Review (SLR) method, which is a structured method for studying relevant literature. The result of data collection through Google Scholar produced 81 relevant scientific articles over the 2019-2023 period. The results of this research showed that mobile application development trends in Indonesia include 5G, artificial intelligence, machine learning, internet of things, augmented reality, and blockchain. From the results of the review that has been conducted, augmented reality became the trend of mobile application development that dominated Indonesia.